Digitization of Osijek grammar school reports at the Library department of the Museum of Slavonia : Digitalizacija izvještaja osječkih gimnazija u Odjelu knjižnice Muzeja Slavonije - Erl Šafar, Marija (Array, 2019)
In the second half of the 19th century, the preconditions for the establishment of standardized school infrastructure were created in Croatia, which also had an impact on the appearance of school libraries. Ever since the onset, the school libraries have played an enlightenment and educational role in their areas and have been maintained as such until present time. Observing the future from a past perspective, it may be noticed that cultural institutions - archives, libraries and museums – in addition to their traditional function, have been developing new types of service under the influence of global information changes that determine new ways of knowledge mediation and management. The annual school reports of end of 19th century Osijek grammar schools, owned by the Library Department of the Museum of Slavonia in Osijek, are an invaluable and indispensable resource for studying the history of schooling, as well as monitoring the development of school librarianship. In this regard, having inspected the contents of the reports of Realna gimnazija (Realgymnasium) and Kraljevska velika gimnazija (Royal Grammar School) of Osijek, it has become evident that there is a need for the creation of a digital repository with the aim of providing protection and a simplified access to and the usage of the aforementioned originals. Such an approach would at the same time enhance the research process of linking metadata from the available historical records, and putting it in the wider context of cultural and historic resources of the City of Osijek.